Different effects of prolonged β-adrenergic stimulation on heart and cerebral artery - Eunji Shin; Kyung Soo Ko; Byoung Doo Rhee; Jin Han; Nari Kim (Integrative Medicine Research)
The aim of this review was to understand the effects of β-adrenergic stimulation on oxidative stress, structural remodeling, and functional alterations in the heart and cerebral artery. Diverse stimuli activate the sympathetic nervous system, leading to increased levels of catecholamines. Long-term overstimulation of the β-adrenergic receptor (βAR) in response to catecholamines causes cardiovascular diseases, including cardiac hypertrophy, stroke, coronary artery disease, and heart failure. Although catecholamines have identical sites of action in the heart and cerebral artery, the structural and functional modifications differentially activate intracellular signaling cascades. βAR-stimulation can increase oxidative stress in the heart and cerebral artery, but has also been shown to induce different cytoskeletal and functional modifications by modulating various components of the βAR signal transduction pathways. Stimulation of βAR leads to cardiac dysfunction due to an overload of intracellular Ca2+ in cardiomyocytes. However, this stimulation induces vascular dysfunction through disruption of actin cytoskeleton in vascular smooth muscle cells. Many studies have shown that excessive concentrations of catecholamines during stressful conditions can produce coronary spasms or arrhythmias by inducing Ca2+-handling abnormalities and impairing energy production in mitochondria, In this article, we highlight the different fates caused by excessive oxidative stress and disruptions in the cytoskeletal proteome network in the heart and the cerebral artery in responsed to prolonged βAR-stimulation.